Genômica comparativa de leveduras probióticasi: Saccharomyces cerevisiae UFMG A-905 e cepas de Saccharomyces boulardii - Thiago Mafra Batista (2015)
Probiotics are living microorganisms present in food and supplements that when ingested in sufficient amounts can confer health benefits. The yeast Saccharomyces cerevisiae var. boulardii was isolated by Henri Boulard in 1920 during a cholera outbreak in Indochina (current Vietnam). S. boulardii is non-pathogenic, thermotolerand and the only eukaryotic microorganism commercialized worldwide as a probiotic for the treatment of human gastrointestinal disorders. The yeast Saccharomyces cerevisiae UFMG A-905 was isolated from a collection of S. cerevisiae that was tested in vitro using simulated gastrointestinal conditions. It has also been tested in vivo for its ability to colonize mice gastrointestinal tract without causing any pathology. Recently, its prottective effect was demonstrated over gnotobiotic animals challenged with Salmonella typhimurium, Escherichia coli and Clostridium difficile, thus characterizing the first potential probiotic product of a Brazilian origin. In this study, we present the genome sequence of UFMG A-905 and three S. boulardii strains. All strains have characteristic S. cerevisiae genome sizes between 11.4Mb and 11.6Mb and on average 5,350 predicted protein-coding genes. The number of gene ontology terms, protein domains and Enzyme Code counts were similar between the probiotic strains, although only the Sb_ATCC MYA-796 strain has substantial evidence of enrichment of the functional category Protein Binding, when compared to the non-probiotic S288c strain. The phylogenetic relationships inferred from the alignment of 415 orthologous proteins and construction of a mega-tree by the Neighbor-Joining method revealed the clustering of three major clades, composed by strains of industrial importance, laboratory strains and alcoholic fermentation strains, which were grouped in a monophyletic branch of probiotic strains. Analyses of SNVs suggest a conservation of variants in probiotic genomes, with an average of 51,943 variants per genome (one variant every 230 bases) and 70% of the predicted impacts of these variants are shared among all four genomes. Twenty unique genes were found to be present in probiotic strains and absent in the non-probiotic strain S288c, most of these coding for proteins with unknown function. We found 803 S288c genes that were absent in the probiotic strains, being 706 common to all four strains, coding mostly for protein related to transposition activity and retrotransposons. The absence of genes related to the influx of protons and ions, as well as heat shock proteins and chaperones, suggests an indirect involvement in the cell resistance to acid stress